Passive multi-unit field-pilot for acid mine drainage remediation: Performance and environmental assessment of post-treatment solid waste. (March 2022) - Vasquez, Yaneth; Neculita, Carmen M.; Caicedo, Gerardo; Cubillos, Jairo; Franco, Jair; Vásquez, Mario; Hernández, Angie; Roldan, Fabio
Abstract: This study evaluated the performance of a passive multi-unit field-pilot operating for 16 months to treat acid mine drainage (AMD) from a coal mine in Colombia Andean Paramo. The multi-unit field-pilot involved a combination of a pre-treatment unit (550 L) filled with dispersed alkaline substrate (DAS), and six passive biochemical reactors (PBRs; 220 L) under two configurations: open (PBRs-A) and closed (PBRs-B) to the atmosphere. The AMD quality was 1200 ± 91 mg L −1 Fe, 38.0 ± 1.3 mg L −1 Mn, 8.5 ± 1.6 mg L −1 Zn, and 3200 ± 183.8 mg L −1 SO4 2−, at pH 2.8. The input and output effluents were monitored to establish AMD remediation. Physicochemical stability of the post-treatment solids, including metals (Fe 2+, Zn 2+, and Mn 2+ ) and sulfates for environmental contamination from reactive mixture post-treatment, was also assessed. The passive multi-unit field-pilot achieved a total removal of 74% SO4 2−, 63% Fe 2+, and 48% Mn 2+ with the line of PBRs-A, and 91% SO4 2−, 80% Fe 2+, and 66% Mn 2+ with the line of PBRs-B, as well as 99% removal for Zn 2+ without significant differences ( p < 0.05 ) between the two lines. The study of the physicochemical stability of the post-treatment solids showed they can produce acidic leachates that could release large quantities of Fe and Mn, if they are disposed in oxidizing conditions; contact with water or any other leaching solutions must be avoided. Therefore, these post-treatment solids cannot be disposed of in a municipal landfill. The differences in configuration between PBRs, open or closed to the atmosphere, induced changes in the performance of the passive multi-unit field-pilot during AMD remediation. Graphical abstract: Image 1 Highlights: Passive multi-unit systems are sustainable for remediation of acid mine drainage. Pretreatment is necessary to maintain the effectiveness of the next treatment unit. Passive systems configuration relates to changes in properties of the reactive mixture. Pos-treatment solid waste should be assessed before disposal in a municipal landfill.